Right to Free and Compulsory Education in India : Constitutional Perspective - Dharm, Jyoti.S; Shringarpure, Salil (International Journal of Psychosocial Rehabilitation, 2020)
A Constitution is the vehicle of Nation’s progress. It is legal as well as social document Indian constitutional law being the Fundamental Law, is a sacred law. The aim of the constitution makers is reflected in the Preamble and in the other provisions of the Constitution. Education as a tool is the most important mechanism for the development of Human beings. Right to education as a fundamental right is inserted in part III of the Constitution. This paper significantly aims to explain the various provisions of the Constitution related to the right to education as a fundamental right.